URGENSI PERLINDUNGAN SAKSI DAN KORBAN DALAM SISTEM PERADILAN PIDANA DI INDONESIA - M. Arif Setiawan (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2008)
The success of the criminal proceeding system highly depends on the evidence revealed. The fact is that the criminal procedure recognized various type of evidence and witness testimonial is considered by the law enforcement i.e Police, State Attorney, or Judge as a key factor to determine the success of a conviction process. So important that it is seen insufficient for a conviction process to stand with the absence of witness testimony. Nevertheless, the attention given to secure the interest of the witness or the victim is not sufficient compared to the usage of witness in revealing crimes. Many people are reluctant in testifying by the reason of security, fear of intimidation by the law enforcement or suspect, time and financial loss without reimbursement, etc. Regardless its several advantages and weaknesess, the existence of Act No.13 Year 2006 (Undang-undang No. 13 tahun 2006) regarding Witness and Victim Protection, is expected to improve the position of the victim and the witness within the criminal proceeding system in order to endorse people who are knowing, hearing, or even suffer from a certain crime to testify before a criminal proceeding.